# Integral of Distribution Function

## Theorem

Let $\struct {X, \Sigma, \mu}$ be a measure space and $f$ be a $\mu$-measurable function. Let $p > 0, r \geq 0$.

For $\lambda > 0$, let $E_\lambda = \set {x \in X: \size {\map f x} > \lambda}$, so that $\map m \lambda = \map \mu {E_\lambda}$ is the distribution function of $f$.

Then:

$\ds \int_0^\infty p \lambda^{p - 1} \int_{E_\lambda} \size f^r \rd \mu \rd \lambda = \int_X \size f^{p + r} \rd \mu$

and in particular:

$\ds \int_0^\infty p \lambda^{p - 1} \map m \lambda \rd \lambda = \int_X \size f^p \rd \mu$

## Proof

 $\ds \int_0^\infty p \lambda^{p - 1} \int_{E_\lambda} \size f^r \rd \mu \rd \lambda$ $=$ $\ds \int_0^\infty \int_{E_\lambda} p \lambda^{p - 1} \size f^r \rd \mu \rd \lambda$ $\ds$ $=$ $\ds \int_X \int_0^{\size {\map f x} } p \lambda^{p - 1} \size f^r \rd \lambda \rd \mu$ by Tonelli's Theorem $\ds$ $=$ $\ds \int_X \size f^r \int_0^{\size {\map f x} } p \lambda^{p - 1} \rd \lambda \rd \mu$ $\ds$ $=$ $\ds \int_X \size f^r \size f^p \rd \mu$ by Integral of Power $\ds$ $=$ $\ds \int_X \size f^{p + r} \rd \mu$

We have that for any measurable $A \in \Sigma$:

$\map \mu A = \ds \int_A 1 \rd \mu$

Therefore, for $\lambda > 0$:

$\map \mu {E_\lambda} = \ds \int_{E_\lambda} 1 \rd \mu$

which can also be written:

$\map \mu {E_\lambda} = \ds \int_{E_\lambda} \size f^0 \rd \mu$

Therefore, taking $r = 0$ in the above, we obtain:

 $\ds \int_0^\infty p \lambda^{p - 1} \map m \lambda \rd \lambda$ $=$ $\ds \int_0^\infty p \lambda^{p - 1} \int_{E_\lambda} \size f^0 \rd \mu \rd \lambda$ $\ds$ $=$ $\ds \int_X \size f^p \rd \mu$

$\blacksquare$